An Analysis Of Figurative Language In William Shakespeare’s Sonnets - Muhammad Azzam Al-mujadid; Devian Try Gustary (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Shakespeare's sonnets are renowned for their profound use of rich metaphors and sophisticated language to explore human emotions and experiences. In three well-known sonnets—